1967
DOI: 10.1097/00007890-196711000-00044
|View full text |Cite
|
Sign up to set email alerts
|

Primary immune response in grafted cells. Dissociation between the proliferation of activity and the proliferation of cells

Abstract: 967 968 PRIMARY IMMUNE RESPONSE IN GRAFTED CELLS Materials and MethodsAnimals.--Outbred eggs (preliminary experiments) were a cross between closed flocks of Rhode Island Red and Light Sussex (purchased from the Appleby Farm Ltd., Ashford, Kent, England). Highly inbred lines of White Leghorns, I and W, were maintained by Dr. D. G. Gilmour at the School of Agriculture, University of Cambridge, from where we obtained birds for production of F1 hybrid embryos. Fertility was low, hence we were much restricted in su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1968
1968
1975
1975

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…Our own studies show that embryonic spleen cells, while able to respond in allogeneic interactions (Killby et al, 1972), are unable to stimulate the proliferation of adult allogeneic leucocytes in MLC (LafFerty et al, 1972). Similarly, the work of Nisbet and Simonsen (1967) shows that spleen cells in the young Fj hybrid chicken embryo, while able to proliferate following contact with adult P strain leucocytes, are unable to stimulate the proliferation of these P strain cells. Thus, while we agree with von Boehmer's proposition (von Boehmer, 1974) that cells other than those capable of immunological recognition may proliferate in allogeneic interactions, we cannot accept the mechanistic basis of recoil activation, namely, the postulate that the a+/aĩ nteraction alone is a sufficient stimulus for the activation of an immunocompetent cell.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Our own studies show that embryonic spleen cells, while able to respond in allogeneic interactions (Killby et al, 1972), are unable to stimulate the proliferation of adult allogeneic leucocytes in MLC (LafFerty et al, 1972). Similarly, the work of Nisbet and Simonsen (1967) shows that spleen cells in the young Fj hybrid chicken embryo, while able to proliferate following contact with adult P strain leucocytes, are unable to stimulate the proliferation of these P strain cells. Thus, while we agree with von Boehmer's proposition (von Boehmer, 1974) that cells other than those capable of immunological recognition may proliferate in allogeneic interactions, we cannot accept the mechanistic basis of recoil activation, namely, the postulate that the a+/aĩ nteraction alone is a sufficient stimulus for the activation of an immunocompetent cell.…”
Section: Introductionmentioning
confidence: 86%
“…In the case of CvH reactions initiated by the introduction of donor lymphoid cells into immunologically immature allogeneic or .semi-allogeneic recipients, snch as the chicken einbrvo, the pathogenesis will be controlled by interaction 6; the Sab cells are immunocompetent lymphoid cells in the donor cell population and "Rag cells are immature haemopoietic cells of the recipient. If the recipients are immunologically immature, all proliferating cells will be of host origin because immunocompetent cells capable of stimulating responsive cells in the donor inoculum will be absent from the embryo (Nisbet and Simonsen, 1967). When donor cells are introduced into older embryos or neonatal animals the situation will be more complex, becanse interaction 5 will come into play when the recipient begins to acquire its own complement of immunocompetent stimulator cells.…”
Section: Hnplicatiom Of the Modelmentioning
confidence: 99%
“…When discussing antigen responsiveness we emphasized that the response of lymphocytes, in either the T or B line, to contact with foreign antigen involved the proliferation of antigen sensitive ceils. This is not always the case in GVH reactions since very strong GVH reactions may be initiated in the absence of any donor cell proliferation (Nisbet & Simonsen 1967).…”
Section: Anomolous Features Of the Gvh Reaction A Characteristics Ofmentioning
confidence: 99%
“…They develop in the spleen and other haemopoietic tissues and are also found as pocks on the CAM (Simonsen 1962). Chromosome analysis has shown that intense host cell proliferation may occur in these lesions without any significant multiplication of donor cells if GVH reactions are initiated between the 10th and 14th day of embryonic life (Nisbet & Simonsen 1967, Weber 1970.…”
mentioning
confidence: 99%
“…These data indicate that specificity exists in T-immune cells, although this specificity might be less evident than in B-cells. One of the main arguments in favour of this low specificity is the high number of antigen-sensitive cells found in a pure T-cell system, like graft versus host (GVH) (Nisbet and Simonsen, 1967) and mixed lymphocyte culture (MLC) (Wilson, Klyth, and Nowell, 1968). This high percentage, 1 to 2 per cent.…”
Section: Specificity At the T-cell Levelmentioning
confidence: 99%